Ductile failure analyses on massively parallel computers - Mathur, K.K.; Needleman, A.; Tvergaard, V. (Computer methods in applied mechanics and engineering, 1994)
Full three-dimensional analyses of ductile failure are carried out for tensile test specimens under dynamic loading, using a data parallel implementation of a ductile porous material model in a transient 3D finite element program. The elastic-viscoplastic material model accounts for ductile failure by the nucleation, growth and coalescence of micro-voids. Most of the results are obtained using 20 node isoparametric brick elements and reduced (2×2×2) quadrature. The capabilities of the model are checked by a number of simulations for one layer of elements subject to overall plane strain conditions, compared to plane strain predictions. Comparisons are made with results using other orders of interpolation and other quadrature rules. It is shown that the high order 3D elements give a good representation of shear localization. For a uniaxial tensile test specimen with a square cross-section, full three-dimensional computations are carried out with meshes consisting of many brick elements in each coordinate direction, and these analyses are used to study the final failure mode in the neck region. The scalability of the parallel implementation is verified and the performance with the porous plastic constitutive relation is compared with that obtained using a standard isotropic hardening model.